Cytologic Changes in Dog Lungs Induced by Chronic Exposure to Ozone - Stephens, Robert J. (1973)
Beagle dogs exposed for 8 hours a day to 3 ppm O(3) for 18 months showed cytologic changes that indicate metabolic alterations. The endoplasmic reticulum of the type 2 alveolar epithelial cells in the proximal alveoli were frequently dilated and contained a moderately electron-dense substance having a periodicity of approximately 754 A. This condition was accompanied by a substantial reduction in the lamellar membranes in the characteristic lamellar bodies of the type 2 cells, suggesting a sequestering of protein in the endoplasmic reticulum. In addition, endothelial cells contained paracrystalline arrays of cytoplasmic membranes not observed in control animals.